Concrete Durability by using Ground Granulated Blast Furnace Slag as A Cement Substitution Against Sulfuric Acid and Chloride Penetration - Khoiru Mardiansyah; Agung Sumarno (Journal of World Conference (JWC), 2021)
It seems that improvements in cement production technology couldn’t be expected to suppress carbon dioxide production significantly. Replacement of some parts of cement in the concrete manufacturing process, or in total replacing them with other more environmentally friendly materials becomes a more promising choice. Along with the increasing demand of concrete to serve the needs of construction in Indonesia is growing as well as innovations developed in the manufacture of concrete. One of them is the use of used materials or waste that can be utilized as add material or substitute cement as an alternative ingredient in concrete mixture. The purpose of this research is to find out the durability of concrete with substitution of Ground Granulated Blast Furnace Slag (GGBFS) against the penetration of sulfuric acid (H2SO4), the penetration of natrium chloride (NaCl) which also review the results of workability, change in density, into the penetration of sulfuric acid and compressive strength. The more the use of ground granulated blast furnace slag (GGBFS), the stronger it is to withstand the penetration of natrium chloride (NaCl). The average concrete density increased by 0.40%, the biggest change was at TM GGBFS 80% by 0.55%. With or without the use of ground granulated blast furnace slag (GGBFS) in the mixture of reinforced concrete acid sulfate (H2SO4) cannot enter into the concrete reviewed from the results of the titration Phenolphthalein is C20H14O4 (pH indicator) the entire concrete surface has been cut in magenta color (base or pH > 8.3). The use of ground granulated blast furnace slag (GGBFS) in the optimum concrete mixture is able to withstand the penetration of sulfuric acid (H2SO4) and the penetration of natrium chloride (NaCl) at the age of 14 days with the substitution of 80% GGBFS which is reviewed from the results of compressive strength concrete.